Assessment of the macroalgal genetic resources maintained in European germplasm banks - Laurie Carol Hofmann; Inka Bartsch; Hendrik Pehlke; Cicero Alves-Lima; Luís M. Barreto; Ricardo Bermejo; Susana Coelho; Olivier De Clerck; Bente Edvardsen; Svenja Heesch; Vladyslava Hostyeva; Lucie Jaugeon; et al. (Journal of Applied Phycology, 2026)
Germplasm banks are important for preserving genetic diversity, yet the availability and long-term maintenance of macroalgal strains in germplasm banks is currently limited in European collections. To support future food security, restoration efforts, and biotechnological innovation, a strategy was recently developed for the long-term preservation of macroalgal genetic diversity. A foundational step in this effort is to assess the existing biodiversity, biogeographical distribution, and commercial relevance of seaweed cultures maintained in European collections. Using a universal data-collection template distributed widely across European seaweed networks, we compiled and analysed information on these seaweed cultures. As of November 2025, the resulting SeaStrains Database of European Seaweed Collections contains 2541 cultures representing 426 species, accounting for only 4% of global and 15% of European macroalgal diversity. The dataset reveals strong taxonomic bias: 74% are brown seaweeds (Ochrophyta), dominated by Laminaria , Saccharina , and Ectocarpus . Saccharina latissima is the most preserved species due to its scientific and commercial importance. Red and green algae are markedly underrepresented (11% and 14%, respectively), likely reflecting cultivation challenges and life-cycle knowledge gaps. Biogeographically, most cultures originate from cold- to warm-temperate zones, with limited representation of the South Atlantic, Indian Ocean, polar and remote regions. Over 60% of cultures are maintained at two institutions: the Culture Collection of Algae and Protozoa (Scotland) and the Alfred Wegener Institute (Germany). This work provides transparent, accessible information on Europe’s macroalgal germplasm resources and represents a crucial step toward a more robust and sustainable European seaweed sector aligned with UN SDG Target 2.5.